Peran Digital Marketing Dalam Menciptakan Brand Equity Rumah Sakit Jih Yogyakarta 2025 - Tri Puji Astuti; Dwi Maharani; Agatha Yesia Rustania (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
The development of digital technology has transformed the way hospitals communicate with the public. Digital marketing functions not only as a promotional medium but also as a strategic approach to building brand equity through the dissemination of health information, strengthening public trust, and fostering relationships with the community. This study aims to analyze the role of digital marketing in creating brand equity at JIH Hospital Yogyakarta and to identify the challenges in its implementation. The study employed a qualitative approach using a case study method within a constructivist paradigm. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using data reduction, data display, and conclusion drawing. The findings indicate that digital marketing contributes to building brand equity through the implementation of the 7Ps marketing mix, including service information delivery, pricing transparency, integrated digital channels, content-based promotion, human resource development, integrated digital services, and strengthened physical evidence. These strategies enhance brand awareness, brand association, perceived quality, and public trust. The main challenges include changes in digital consumer behavior, platform algorithm dynamics, content consistency, ethical health communication, and maintaining a consistent digital patient experience.